Desertihabitans brevis sp. nov., an actinobacterium isolated from sand of the Taklamakan desert, and emended description of the genus Desertihabitans. Issue 2 (26th November 2019) - Liu, Shao-Wei; Li, Fei-Na; Liu, Hong-Yu; Yu, Li-Yan; Sun, Cheng-Hang
Abstract : A novel actinobacterium, designated strain 16Sb5-5 T, was isolated from a sand sample collected in the Taklamakan desert in Xinjiang Uygur Autonomous Region, China. The strain was examined by a polyphasic approach to clarify its taxonomic position. Cells of the isolate were Gram-staining-positive, aerobic, non-motile and short-rod shaped. Strain 16Sb5-5 T grew optimally at 37 °C, pH 7.0 and with 0‒2 % (w/v) NaCl. The cell-wall peptidoglycan was of the A3 γ type and contained alanine, glycine, glutamic acid and ll -diaminopimelic acid (ll -DAP). Ribose, arabinose and glucose were detected in the whole-cell hydrolysates. The predominant menaquinone was MK-9(H4 ). The polar lipid profile consisted of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, an unidentified phospholipid, three unidentified glycolipids and three unidentified lipids. The major whole-cell fatty acids were anteiso-C15 : 0 and iso-C15 : 0 . Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain 16Sb5-5 T was closely related to Desertihabitans aurantiacus CPCC 204711 T (99.8 % similarity) and formed a robust clade with D. aurantiacus in the phylogenetic trees. In silico genomic comparisons showed that strain 16Sb5-5 T exhibited ANI values of 94.8–94.9 % and GGDC value of 59.5 % to D. aurantiacus CPCC 204711 T . The genomic G+C content was 73.3 mol%. On the basis of phylogenetic, phenotypic and chemotaxonomic analyses, strain 16Sb5-5 T could be distinguishable from its closest phylogenetic relative and represents a novel species of the genus Desertihabitans, for which the name Desertihabitans brevis sp. nov. is proposed. The type strain is 16Sb5-5 T (=KCTC 49116 T =CGMCC 1.16553 T ). The description of the genus Desertihabitans has also been emended.